Improvement Of Didactic Adaptation of Young Teachers to Conditions of Higher Education Based on Credit Module System (Eurasian Journal of Learning and Academic Teaching, 2022)
The article focuses on the issues of didactic orientation and improvement of pedagogical skills of professors to this system as a result of the introduction of credit-module system in higher and higher special education.